Headache in stroke according to National Acute Stroke Israeli Survey. (20th June 2016) - Pollak, L.; Shlomo, N.; Korn Lubetzki, I.; ,
Abstract : Objectives: Analysis of headache occurrence in a national cohort of patients with acute stroke. Methods: The data were based on the triennial 2‐month period of the National Acute Stroke Israeli (NASIS) Registry. A total of 2166 patients with acute stroke were retrieved: 2001 (92.4%) had ischemic stroke (IS), 150 (6.9%) had intracerebral hemorrhage (ICH), 4 (0.2%) had sinus vein thrombosis (SVT), where as in 11 (0.5) the stroke type was undetermined. Results: Two hundred and six (9.5%) patients reported headache: in SVT headache was reported by 50% of patients, in ICH by 21.3% while 8.4% of patients with IS (28% with transient ischemic attack [TIA]) complained about headache. In 18.1% of patients with headache, the stroke type was undetermined. Female gender, younger age, previous headache, cerebral hemorrhage, and dizziness/unsteadiness predisposed for headache. The incidence of headache was higher in patients with ICH than in patients with IS regardless of the history of previous headaches. In IS, headache decreased with stroke severity and was more common in the posterior than in the anterior circulation. Patients with lacunar stroke suffered less frequently from headache than patients with non‐lacunar stroke. Significantly more patients with carotid dissection presented with headache than without. Conclusions: Intracerebral hemorrhage, younger age, female gender, posterior circulation involvement, and headache history are predictors for headache occurrence in acute stroke. Headache incidence in ICH correlates with stroke severity as opposed to IS. Headache in TIA is not unusual. Lacunar strokes are generally not accompanied by headaches. Headache remains the main complaint in SVT and carotid dissection.